Pandangan Islam Terkait Gender (Bissu, Calalai, Calabai, Makkunrai, dan Urane) - Marliana; Amir, Afriandi; Haerah, Magefiratul; Hidayat M, Rahmatul; Mirnawati; Azisa, Kurnia (Palakka : Media and Islamic Communication, 2025)
This research examines the relationship between Islamic values and the unique gender system in Bugis society in South Sulawesi, Indonesia, which recognizes five gender identities: makkunrai, urané, calalai, calabai, and bissu. Using a descriptive qualitative approach and literature study methods, this research analyzes the cultural, spiritual, and religious aspects of non-binary gender roles in Muslim society. Data were obtained from scientific journals, books, reports, and relevant digital sources related to the topic. The findings indicate that the Bugis community negotiates between Islamic teachings and local traditions, resulting in contextual interpretations that embrace gender diversity. The bissu figure is viewed as a sacred entity and plays an important role in customary ceremonies and the spirituality of the community. Gender identity in Bugis society is understood not only from a biological perspective but as a result of the dynamic interaction between religion, culture, and evolving social roles. This research contributes to the discourse on Islam regarding gender diversity and emphasizes the importance of preserving local wisdom amid the pressures of globalization and conservative religious ideologies. The study recommends a more contextual and humanistic Islamic approach to understanding the diverse social realities.